2022
DOI: 10.1002/alz.12718
|View full text |Cite
|
Sign up to set email alerts
|

Toward rational use of cognitive training in those with mild cognitive impairment

Abstract: The term cognitive training includes a range of techniques that hold potential for treating cognitive impairment caused by neurologic injury and disease. Our central premise is that these techniques differ in their mechanisms of action and therefore engage distinct brain regions (or neural networks). We support this premise using data from a single-blind randomized-controlled trial in which patients with mild cognitive impairment were randomized to either mnemonic strategy training (MST) or spaced retrieval tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…This trend suggests that the brain may be adapting and becoming more interconnected in response to cognitive training, even if the changes are not yet statistically significant. Previous studies on cognitive training in Alzheimer's disease (AD) and older adults have also reported elevated FC in various brain regions within brain networks, which aligns with our study's findings 36,37 . It is noteworthy that our study divided different functional brain networks and further explored the changes in the FC attributes of the network, suggesting that the global brain network connectivity attributes increased significantly with computerized cognitive training.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This trend suggests that the brain may be adapting and becoming more interconnected in response to cognitive training, even if the changes are not yet statistically significant. Previous studies on cognitive training in Alzheimer's disease (AD) and older adults have also reported elevated FC in various brain regions within brain networks, which aligns with our study's findings 36,37 . It is noteworthy that our study divided different functional brain networks and further explored the changes in the FC attributes of the network, suggesting that the global brain network connectivity attributes increased significantly with computerized cognitive training.…”
Section: Discussionsupporting
confidence: 90%
“…36 In this study, we suggest that the observed decrease in FC in larger-scale intra-networks is (AD) and older adults have also reported elevated FC in various brain regions within brain networks, which aligns with our study's findings. 36,37 It is noteworthy that our study divided different functional brain networks and further explored the changes in the FC attributes of the network, suggesting that the global brain network connectivity attributes increased significantly with computerized cognitive training. Furthermore, the SMN and the LN, functioning as primary networks, are responsible for controlling sensorimotor and language processing functions, respectively.…”
Section: Separation and Integration Of Brain Networkmentioning
confidence: 99%
“…These results are consistent with studies on the effects of mnemonic strategy training with older adults with SCD or MCI, 40,41 and imaging results of mnemonic strategy training have shown improvements in brain activity. 15,42 In a study of older adults with SCD, participants tended to spontaneously use more mnemonic strategies to compensate for the memory decline they experienced, and using the strategies in everyday life situations made them more beneficial. 43 This study suggests that the effectiveness of emphasizing mnemonic strategy training in a multicomponent intervention may have a positive effect on the more effective implementation and use of mnemonic strategies in daily life to consistently strengthen memory in older adults at risk of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 One such intervention is a widely used form of cognitive training based on mnemonic strategies, which has demonstrated good results in improving cognitive function for individuals with MCI and SCD. [14][15][16][17] Mnemonic strategies can be widely conceptualized as cognitive methods that contribute to the organization and association of new information, thus increasing the depth of processing. 18 Mnemonic-strategy interventions usually include teaching participants about brain structure, how memory functions, and training memory strategies and guiding their application in everyday life.…”
mentioning
confidence: 99%